Assessment of Genetic Diversity of the Wild Rice (Oryza longistaminata) Populations in Tanzania Using Microsatellite Markers - Mangosongo, Hashim M.; Mneney, Emerald E.; Harvey, Jagger; Kyallo, Martina (Tanzania Journal of Science, 2020)
The genetic diversity of 132 samples of the perennial wild rice (Oryza longistaminata) populations from selected districts (Bagamoyo, Kibaha, Kilombero and Mbarali) in Tanzania was evaluated using twenty eight microsatellite markers. Genomic DNA was extracted using standard protocols. Polymerase Chain Reaction (PCR) was carried out in a total reaction volume of 10 µL, using Touchdown protocol. It was found that all 28 microsatellite markers generated polymorphic patterns, with average Polymorphic Information Content (PIC) value of 0.631. Moreover, a total of 243 alleles were detected by the 28 markers, with average of 8.68 alleles per marker. The percentages of genetic variations among and within populations were 10% and 90%, respectively, implying that there was more gene flow among populations than within populations. Furthermore, the O. longistaminata population from Kilombero had highest genetic diversity followed by population from Mbarali, while the lowest genetic diversity was recorded in the population from Kibaha. Generally the populations from Kilombero, Mbarali and Bagamoyo were found to have relatively high genetic diversity, hence have potential to be used in rice breeding. In situ conservation of this species is recommended, and it can be achieved by conserving all areas which harbour populations with high levels of genetic diversity.